NOAC (North Atlantic Changes) - Cruise No. MSM28 - May 09 - June 20, 2013 - St. John's (Canada) - Tromsø (Norway) - Kieke, Dagmar; Abels, Lotte; Böke, Wolfgang; Bulsiewicz, Klaus; Denker, Claudia; Hauck, Dennis; Hertzberg, Stefan; Koopmann, Nikolaus; Lahl, Rebecca; Lange, Julia; Löb, Jonas; Müller, Vasco; et al. (DFG-Senatskommission für Ozeanographie, 2014)
Cruise MSM-28 was dedicated to investigating the circulation system and the water mass structure in the western subpolar North Atlantic. A special focus was on the Labrador Sea, the Newfoundland Basin and the West European Basin. One of the objectives of cruise MSM-28 was to obtain a large-scale water mass inventory regarding the anthropogenic tracers SF6 and CFC-12. These will serve to estimate spreading and aging of Labrador Sea Water (LSW) and allow for inferring respective formation rates since 2011. Two mooring arrays recovered during cruise MSM-27 in Flemish Pass and in the region of the DWBC off Flemish Cap were intended to be redeployed again during cruise MSM-28. Due to severe instrument loss (one DWBC mooring could not be recovered during cruise MSM-27) the deployment of the DWBC array was entirely canceled, and the instruments were brought to Bremen for further inspection. As another consequence resulting from the instrument loss the redeployment of the Flemish Pass mooring array, by intention shifted from cruise MSM-27 to cruise MSM-28, was reduced to one out of two moorings. Canadian partners from the Bedford Institute of Oceanography in Dartmouth/Canada, however, deployed a second mooring in the Labrador Current passing through Flemish Pass in June 2013. So, this array presently consists of two moorings, though with adjusted locations. The deep-sea mooring array located at the western flank of the Mid-Atlantic Ridge (MAR) was successfully recovered and, extended by a fourth mooring, redeployed again at the MAR. Along the same line four inverted echo-sounders equipped with pressure sensors (PIES) were serviced, and four additional instruments were deployed in the Newfoundland Basin along 47°N. These instruments serve to estimate variations of baroclinic and barotropic transports of the subpolar gyre. Measurements carried out during cruise MSM-28 and corresponding results contribute to the BMBF-funded project RACE, WP 1.2, and to the DFG-funded project FLEPVAR. : MARIA S. MERIAN-Berichte